Crystal structure of chlorido{hydridotris[3-phenyl-5-methylpyrazol-1-yl-κN3]borato}copper(II), C30H28BClCuN6 - Fujisawa, Kiyoshi; Shimizu, M.; Tiekink, Edward R. T. * (De Gruyter Open, 2021)
C30H28BClCuN6, triclinic, P¯1 (no. 2), a = 11.549(3) Å, b = 12.321(3) Å, c = 12.348(4) Å, α = 111.785(1)°, β = 116.664(3)°, γ = 97.513(1)°, V = 1361.3(7) Å3, Z = 2, Rgt(F) = 0.0440, wRref(F2) = 0.1063, T = 197 K.